Symbolic Islamization and Political Authority in Suluk Linglung of Sunan Kalijaga: Cultural Negotiation and the Formation of Javanese Islamic Legitimacy - Fatchullah Zarkasi; Mustolehudin; Siti Nursyamsiyah; Hafiz Abdullah (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
The formation of Islamic authority in Indonesia did not occur solely through formal political institutions but operated dynamically through cultural negotiation and spiritual legitimacy. Although the Islamization of Java has been extensively studied, mainstream political thought often reduces authority to state-centric power structures, leaving the role of symbolic practices in classical vernacular texts underexplored. This study analyzes the dimensions of Islamic political thought in the Suluk Linglung manuscript, a text representing the teachings of Sunan Kalijaga within the socio-political landscape of early Java. Employing a descriptive text and qualitative content analysis approach, this study compares two printed versions of the manuscript to decode its cultural metaphors. The findings indicate that Suluk Linglung conceptualizes a model of Islamic political authority grounded in symbolic persuasion and spiritual legitimacy rather than coercive domination. Through the philosophical structure of the macapat tradition (specifically Pupuh Dhandhanggula, Asmaradana, Durma, and Kinanthi), the manuscript transforms cultural symbols (such as the metaphors of the honey-seeking bee, the deer, gold, and prostration) into a practical framework for prudence, moral integrity, and leadership responsibility (amanah). This study offers a preliminary theoretical contribution by proposing a "theo-cultural synthesis" model, suggesting how leadership authority may be constructed not through institutional conquest, but through the strategic indigenization of ethical legitimacy.